2010
DOI: 10.4103/0253-7613.70020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rationality of promotional drug literature using World Health Organization guidelines

Abstract: Objectives:The study was aimed to evaluate collected drug promotional brochures for accuracy, consistency, and validity of the information presented in it, using World Health Organization (WHO) criteria for ethical medicinal drug promotion. Drug promotional brochures were evaluated for the type of claims and pictorial content presented in it and for references cited in support of these claims.Material and Methods:This observational, cross-sectional study was conducted in the outpatient department of Government… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
75
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(99 citation statements)
references
References 14 publications
17
75
1
3
Order By: Relevance
“…Similar line of findings was reported from various other studies. [10][11][12][13][14] The pharmaceutical industries rather accomplish their own commercial motive and neglected the ethical educational aspect. This carries a marked impact on the overall health delivery system.…”
Section: Discussionmentioning
confidence: 99%
“…Similar line of findings was reported from various other studies. [10][11][12][13][14] The pharmaceutical industries rather accomplish their own commercial motive and neglected the ethical educational aspect. This carries a marked impact on the overall health delivery system.…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance of information on safety parameters like side effects, major adverse drug reactions, precautions, warnings, major interactions in Indian journals more than in foreign journals might be not to discourage the prescribers from prescribing that product. Mali et al (2010) have also observed mention of safety parameters only in 8.8% of Indian advertisements. 6 Lack of references in Indian journals" advertisements more than foreign journals increases the risk of claims being false.…”
Section: Discussionmentioning
confidence: 99%
“…Mali et al (2010) have also observed mention of safety parameters only in 8.8% of Indian advertisements. 6 Lack of references in Indian journals" advertisements more than foreign journals increases the risk of claims being false. However, compared to another similar study by Lal A et al (1997), the compliance of Indian advertisements to WHO criteria, in this study, has been found to be higher in most of parameters including safety parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations